PENGEMBANGAN KURIKULUM PAI DI SMAN 1 NAWANGAN PACITAN - Khoeron; Haris (Jurnal Pendidikan Islam, 2024)
The purpose of this research is to find out and analyze: the development of the PAI curriculum, at SMAN 1 Funding the level of learning planning that is suitable for the needs of the material to be delivered, then the need for the level of implementation as an implementation or application of the curriculum used and the level of evaluation as a measuring tool for see the achievement of the expected goal. This research is motivated by PAI practices in schools that are less than optimal, especially due to the lack of teaching hours. Seeing this problem, the development of the PAI curriculum becomes very important, the implementation of PAI learning, and the development of PAI evaluation. This research uses the Phenomenological study method by using a qualitative approach. Data collection techniques are done through interviews, observations and documentation studies. Based on the results of the research, it was found that the purpose of developing PAI is to develop academic ability as well as promote the values of Islamic character in students. As for the development of the substance of PAI, it is developed into two forms, namely the intracurricular form, the P5 subject content (a project to strengthen the profile of Pancasila students) integrated with religious values and the form of school culture (school habituation) in the form of the Qur'an Literacy Movement (GERLIQ). . The development of evaluation of the PAI curriculum is carried out by PAI teachers with diagnostic assessment, differentiated learning that focuses on the cognitive domain through formative and summative tests, the psychomotor assessment domain is carried out by performing religious practices that are adapted to the themes studied as well as religious values that are integrated in life in school and the implementation of the Pancasila student profile strengthening project (P5), while the affective evaluation is carried out during the learning process.